2022
DOI: 10.1007/s00284-022-03061-7
|View full text |Cite
|
Sign up to set email alerts
|

Current Treatment Strategies Against Multidrug-Resistant Bacteria: A Review

Abstract: There are several bacteria called superbugs that are resistant to multiple antibiotics which can be life threatening specially for critically ill and hospitalized patients. This article provides up-to-date treatment strategies employed against some major superbugs, like methicillin-resistant Staphylococcus aureus, carbapenem-resistant Enterobacteriaceae, vancomycin-resistant Enterococcus, multidrug-resistant Pseudomonas aeruginosa, and multidrug-resistant Escherichia coli. The pathogen-directed therapeutics de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(36 citation statements)
references
References 86 publications
0
35
0
1
Order By: Relevance
“…One such approach that has gained traction against infectious disease has been host directed therapies, whereby the host cellular processes needed by the pathogen lifecycle are disrupted (33). Other studies have shown this approach to be effective by, for example, disrupting the apoptosis pathway (34,35). Our study has revealed a new possible target for host directed therapy in BIRC5, as conditional deletion of this gene in immune cells significantly improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…One such approach that has gained traction against infectious disease has been host directed therapies, whereby the host cellular processes needed by the pathogen lifecycle are disrupted (33). Other studies have shown this approach to be effective by, for example, disrupting the apoptosis pathway (34,35). Our study has revealed a new possible target for host directed therapy in BIRC5, as conditional deletion of this gene in immune cells significantly improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…infections and even the emergence of various drug-resistant bacteria. 4,5 Moreover, a global report by the World Health Organization (WHO), at least 700 000 people are killed by drug-resistant bacteria annually, and the number will possibly increase to 10 million deaths by 2050 without any prophylactic measures. 6 Interestingly, Gram-negative (G À ) bacteria are more resistant than Gram-positive (G + ) bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, MDR developed and spread more frequently because of incorrect antimicrobial medicine use, unhygienic environments, poor food handling, antibiotics abuse and inefficient healthcare-associated infections strategies [4]. To combat microbial resistance, a variety of measures have been used, including the application of bactericidal agents, emerging novel antibiotics and combined treatment [5][6][7]. Nanotechnology is the science, engineering and application of materials and devices with dimensions on the nanoscale, typically ranging from 1 to 100 nanometers (nm).…”
Section: Introductionmentioning
confidence: 99%